Review of the Phenomenon of Ice Shedding from Wind Turbine Blades - Xue, Hui; Khawaja, Hassan Abbas (The International Journal of Multiphysics, 2016)
Publisher's version, source: http://dx.doi.org/10.21152/1750-9548.10.3.265 . Wind power is a sustainable source of energy. However, there are certain challenges to be overcome. One of the operational challenges is the phenomenon of ice shedding. Icing happens on wind turbine blades in cold regions. When ice grows to a certain size, it separates from the wind turbine blades resulting in the phenomenon of ice shedding. This phenomenon is of significantly dangerous for equipment and personnel in the region. Ice shedding may happen either because of vibrations or bending in blades. However, it was noticed by operators at Nygårdsfjell wind park, Narvik, Norway that ice shedding is more probable to happen when blades are stopped and turned back on. This observation reveals the fact that bending of blades (from loaded to unloaded positions) allows the ice to separate and hence result in ice shedding. This can be linked to the phenomenon of icing, mechanical and adhesive properties of ice. This paper reviews above in detail.